Green Synthesis of ZnO Nanoparticles Using Kalamansi Peel Extract (Citrus Microcarpa Bunge) for Photocatalytic Degradation of Methyl Orange - Evi Maryanti; Eka Angasa; Mega Elfia; Wulan Aprilia Syafitri; Niken Parnia Norda; Eduwin Saputra (Jurnal Kimia Riset, 2026)
This study reports the green synthesis of zinc oxide (ZnO) nanoparticles using kalamansi peel extract (Citrus microcarpa Bunge) as a natural reducing and stabilizing agent, followed by evaluation of their photocatalytic activity toward methyl orange degradation under sunlight irradiation. The synthesis was carried out via a precipitation method using extract concentrations of 2%, 4%, and 6% (w/v) to investigate the effect of bioactive compound content on the structural and photocatalytic properties of ZnO. Higher extract concentrations were expected to provide more phytochemical compounds, which could improve crystal growth control and particle stabilization during synthesis. Characterization by FTIR confirmed the presence of Zn-O and Zn-OH vibrations at 882 cm-¹. XRD analysis revealed diffraction patterns corresponding to the hexagonal wurtzite ZnO phase, with crystallinity increasing from 84.62% to 91.08% as extract concentration increased. SEM observations showed that ZnO synthesized with 2% extract experienced significant agglomeration, while 4% and 6% extract concentrations promoted the formation of irregular tube-like and nanorod morphologies with better particle distribution. EDS analysis verified the presence of Zn and O elements in all samples. Photocatalytic tests demonstrated that ZnO synthesized using 6% extract exhibited the highest degradation efficiency of methyl orange (67.8% after 120 min), which was attributed to its higher crystallinity, reduced agglomeration, and improved nanorod morphology that enhanced light absorption and reactive species generation. These results indicate that extract concentration plays a crucial role in determining the physicochemical properties and photocatalytic performance of green-synthesized ZnO nanoparticles.